Design of Miniaturized FSS with High Angular Stability Utilizing a Novel Closed Loop - Wei Li; Fengshuo Zhang; Ying Suo; Zhe Jiang; Jinghui Qiu (International Journal of Antennas and Propagation)
In this paper, we propose a miniaturized 2.5-dimensional (2.5D) frequency selective surface (FSS) structure with high angular stability. A novel closed-loop FSS is formed by combining the Jerusalem cross (JC) structure with the conventional rectangular closed loop using vias. This approach further enhances the coupling performance of the FSS and thus achieves miniaturized design. The unit cell size of the proposed FSS is 0.019λ0 × 0.019λ0 at the resonant frequency, and the metal is printed on a dielectric substrate with a thickness of 0.003λ0. The proposed FSS has a resonant frequency of 850 MHz and exhibits band-stop characteristics. It is insensitive to the incident angle with a good operating performance in both the TE and TM wave modes. Therefore, it can be well used as an electromagnetic shield for the GSM 850 band. In order to facilitate the rapid analysis and design of the FSS, the equivalent circuit model is further analyzed and established, and values of the corresponding lumped components are derived. In addition, a prototype FSS is fabricated using printed circuit board technology and is tested in a microwave anechoic chamber. The full-wave analysis simulation, equivalent circuit model simulation, and practical measurement results reflect a high level of consistency.